Spatial risk assessment for climate proofing of economic activities: The case of Belluno Province (North-East Italy) - Carlo Giupponi; Giuliana Barbato; Veronica Leoni; Paola Mercogliano; Carlo Papa; Giovanni Valtorta; Michele Zen; Christian Zulberti (Climate Risk Management)
Recent advancements in spatial risk assessment methodologies, particularly those incorporating GIS and economic evaluations, have significantly enhanced our ability to assess and manage risks associated with natural disasters. Entrepreneurs, investors, and public administrations need information about climate change risks for effective planning and decision making. To move from generic global or national projections about climate change scenarios, towards more actionable information on climate risks for socioeconomic agents, the three dimensions of risk (Hazard, Exposure and Vulnerability) must be quantified and mapped with the involvement of stakeholders. In this study, spatial indicators, tailored to the social and ecological systems of interest and co-designed with the key stakeholders are aggregated into sectoral risk indexes quantified in economic terms. Climate risk indexes were calculated and mapped for the four key economic sectors of the study area of the Belluno Province (Italian Alps): summer tourism, winter sports and events, eyewear industry, and electricity supply. Stakeholders were involved during the assessment to share knowledge, data and needs and to provide expert judgments on intermediate and final results. Outputs include a series of maps and statistical summaries, highlighting future trends of climate related risks, their spatial variability within the area and the estimated levels of uncertainty. Estimates on expected changes of future damages with constant Exposure and Vulnerability, provided socioeconomic agents with simple and clear messages about how their activities could suffer or benefit from climate change in the future.